Conflict and agricultural inputs: Impacts on maize yields in Nigeria - Amare, Mulubrhan; Andam, Kwaw S.; Balana, Bedru; Olanrewaju, Opeyemi; Omamo, Steven Were (International Food Policy Research Institute, 2025)
While standard agronomic recommendations advocate for increased application of inorganic fertilizer to boost maize yields across sub-Saharan Africa, there is limited understanding of how violent conflict influences smallholder farmers’ fertilizer demand, yield responses, and the overall profitability of fertilizer use. This study addresses this gap by analyzing how exposure to conflict affects input use decisions and the economic returns to fertilizer among maize farmers in Nigeria. Using detailed household-level data and spatially referenced conflict events, we estimate maize yield response functions with respect to nitrogen application and assess the profitability of fertilizer under varying levels of conflict exposure. Our findings reveal three key results. First, the marginal physical product (MPP) of nitrogen is low across the study sample, indicating limited agronomic responsiveness. Second, conflict exposure significantly reduces the likelihood and intensity of fertilizer use, suggesting that insecurity constrains both input access and willingness to invest. Third, conflict lowers the MPP of nitrogen even further, thereby reducing the marginal value-cost ratio (MVCR) and undermining the profitability of fertilizer use. These results highlight the importance of considering conflict as a key external factor that distorts input-output relationships in agricultural production. Insecurity not only affects access to inputs through higher prices and disrupted supply chains, but also alters expected returns, making fertilizer investments less attractive for risk-averse farmers. Recognizing the effects of conflict on fertilizer use and yield response is essential for designing more effective input subsidy programs, targeting strategies, and resilience-building interventions in fragile agricultural systems.